2000
DOI: 10.1046/j.1365-313x.2000.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of the Brassica napus napin promoter by ABI3 requires interaction of the conserved B2 and B3 domains of ABI3 with different cis‐elements: B2 mediates activation through an ABRE, whereas B3 interacts with an RY/G‐box

Abstract: SummaryThe transcriptional activator ABI3 is a key regulator of gene expression during embryo maturation in crucifers. In monocots, the related VP1 protein regulates the Em promoter synergistically with abscisic acid (ABA). We identi®ed cis-elements in the Brassica napus napin napA promoter mediating regulation by ABI3 and ABA, by analyzing substitution mutation constructs of napA in transgenic tobacco plantlets ectopically expressing ABI3. In transient analysis using particle bombardment of tobacco leaf secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(134 citation statements)
references
References 39 publications
7
124
0
2
Order By: Relevance
“…Consistent with this observation, LEC2, ABI3, and FUS3 share identical or conserved amino acid residues at positions in the B3 domain implicated as being responsible for DNA-binding specificity based on the solution structure of the B3 domain protein RAV1 (41). Thus, all three transcription factors bind RY motifs through their B3 domains and activate maturation-specific genes, although we note that ABI3 activity is influenced by an additional domain that binds ABA response elements (40).…”
Section: Lec2 Directly Activates Genes Involved In Maturation Processessupporting
confidence: 76%
See 1 more Smart Citation
“…Consistent with this observation, LEC2, ABI3, and FUS3 share identical or conserved amino acid residues at positions in the B3 domain implicated as being responsible for DNA-binding specificity based on the solution structure of the B3 domain protein RAV1 (41). Thus, all three transcription factors bind RY motifs through their B3 domains and activate maturation-specific genes, although we note that ABI3 activity is influenced by an additional domain that binds ABA response elements (40).…”
Section: Lec2 Directly Activates Genes Involved In Maturation Processessupporting
confidence: 76%
“…1) (33,36,37). Our demonstration that LEC2 binds with the same DNA element bound by FUS3 and ABI3 (30,(38)(39)(40), the RY motif, provides a partial explanation for similarities in the gain-of-function phenotypes. Consistent with this observation, LEC2, ABI3, and FUS3 share identical or conserved amino acid residues at positions in the B3 domain implicated as being responsible for DNA-binding specificity based on the solution structure of the B3 domain protein RAV1 (41).…”
Section: Lec2 Directly Activates Genes Involved In Maturation Processesmentioning
confidence: 75%
“…Three-hybrid and BiFC analyses confirmed that bZIP heterodimerization of bZIP10 or bZIP25 with bZIP53 does not interfere with ABI3 interaction and supports the existence of a ternary complex. ABI3 has been shown to bind to the RY element (Mö nke et al, 2004), and a functional interplay between G-box and RY-element in MAT gene regulation has been previously described (Ezcurra et al, 2000;Lara et al, 2003). In this report, we clearly demonstrate functional interplay between bZIP heterodimers and ABI3, presumably by ternary complex formation.…”
Section: Bzip53 Group C Bzips and Abi3 Physically And Functionally supporting
confidence: 70%
“…A nativesequence oligonucleotide (wild type) containing a functional bZIP (G-box) binding site (Ezcurra et al, 2000) derived from the 2S2 promoter and a mutated version were used ( Figure 3B). Doublestranded oligonucleotides were covalently attached to 96-well ELISA plates before doing the binding assays as described in Methods.…”
Section: Activation Of the 2s2 Seed Storage Protein Gene By Bzip53 Anmentioning
confidence: 99%
See 1 more Smart Citation